Awareness of COVID-19 among Illiterate Population in Pakistan: A Cross-Sectional Analysis. (9th August 2023) - Salman, Muhammad; Mustafa, Zia Ul; Asif, Noman; Shehzadi, Naureen; Hussain, Khalid; Khan, Tahir Mehmood; Mallhi, Tauqeer Hussain; Khan, Yusra Habib; Butt, Muhammad Hammad; Farrukh, Muhammad Junaid; Saleem, Fahad
Abstract: Background: COVID-19 outbreak has been accompanied by a massive infodemic, however, many vulnerable individuals such as illiterate or low-literate, older adults and rural populations have limited access to health information. In this context, these individuals are more likely to have poor knowledge, attitudes, and preventive practices related to COVID-19. The current study was aimed to investigate COVID-19's awareness of the illiterate population of Pakistan. Methods: A cross-sectional survey was conducted among illiterate Pakistanis of ages ≥ 18 years through a convenient sampling approach. The study participants were interviewed face to face by respecting the defined precautionary measures and all data were entered and analyzed using SPSS version 22 (IBM, Armonk, NY). Results: The mean age of the study participants' (N = 394) was 37.2 ± 9.60 years, with the majority being males (80.7%). All participants were aware of the COVID-19 outbreak and television news channels (75.1%) were the primary source of information. The mean knowledge score was 5.33 ± 1.88, and about 27% of participants had a good knowledge score (score ≥ 7) followed by moderate (score 4 - 6) and poor (score ≤ 3) knowledge in 41.6%, and 31.5% of respondents, respectively. The attitude score was 4.42 ± 1.22 with good (score ≥ 6), average (score 4 - 5), and poor attitude (score ≤ 3) in 19%, 66%, and 15% of the participants, respectively. The average practice-related score was 12.80 ± 3.34, with the majority of participants having inadequate practices. Conclusion: COVID-19 knowledge, attitude, and preventive practices of the illiterate population in Pakistan are unsatisfactory. This study highlights the gaps in specific aspects of knowledge and practice that should be addressed through awareness campaigns targeting this specific population.